Tinjauan Pengembalian Rekam Medis Rawat Jalan Dan Kecepatan Pendistribusian Rekam Medis Ke Poliklinik di Rumah Sakit An-Nisa Tangerang - Raysha Dheamalia Muchtar; Noor Yulia (Indonesian of Health Information Management Journal (INOHIM), 2017)
AbstractTo get the performance of medical record installation of quality the in the implementation of medical record must be done properly and accurately, including on return and distribution of medical record. The return of medical records at An-Nisa Hospital is ≤1x24 hours and the distribution of medical records is ≤ 10 minutes. Delay in the return of medical records and on the distribution of medical records will be disruptive in the medical services that will be given to patients with repeated control. The purpose of this research is to get a description of the return of medical records outpatient and the speed of distribution of medical record to polyclinics at An-Nisa Hospital Tangerang. The research method used is descriptive method. The results of the research on the return of medical records on time 83% and the not on time by 17%. For the average distribution of medical records to the nurse station is 13 minutes. Based on the result of the research, it is known that the return of outpatient medical records and the distribution of medical records has not gone well. The delay in medical record returns is due to no checks on medical records borrowed by those returned by polyclinic nurses and casemix officers. Delays on the distribution of medical records due to >1x24 hour medical record returns. In order for the medical record to run properly, it is necessary to supervise and control the return of medical records.Keywords: Medical Record, Return, Distribution, Outpatient AbstrakUntuk mendapatkan kinerja instalasi rekam medis yang berkualitas maka dalam penyelenggaraan rekam medis harus dilakukan dengan benar dan tepat, termasuk pada pengembalian dan pendistribusian rekam medis. Standar pengembalian rekam medis di Rumah Sakit An-Nisa adalah ≤1x24 jam dan pendistribusian rekam medis adalah ≤10 menit. Keterlambatan dalam pengembalian rekam medis dan pada pendistribusian rekam medis akan mengganggu pelayanan medis yang akan diberikan kepada pasien saat kontrol ulang. Tujuan penelitian ini adalah untuk mendapatkan gambaran mengenai pengembalian rekam medis rawat jalan dan kecepatan pendistribusian rekam medis ke poliklinik di Rumah Sakit An-Nisa Tangerang. Metode penelitian yang digunakan adalah metode deskriptif. Hasil penelitian pada pengembalian rekam medis yang tepat waktu sebesar 83% dan yang tidak tepat waktu sebesar 17%. Rata – rata pendistribusian rekam medis ke nurse station adalah 13 menit. Berdasarkan hasil penelitian tersebut diketahui bahwa pengembalian rekam medis rawat jalan dan pendistribusian rekam medis belum berjalan dengan baik. Keterlambatan pada pengembalian rekam medis dikarenakan tidak ada pengecekan terhadap rekam medis yang dipinjam dengan yang dikembalikan oleh perawat poliklinik dan petugas casemix. Keterlambatan pada pendistribusian rekam medis karena pengembalian rekam medis yang >1x24 jam. Agar pada proses rekam medis bisa berjalan dengan baik maka disarankan adanya pengawasan serta pengontrolan terhadap pengembalian rekam medis.Kata Kunci : Rekam Medis, Pengembalian, Pendistribusian, Rawat Jalan